Pengaruh Harga, Citra Merek, Dan Kualitas Produk Terhadap Minat Beli Produk Eiger (Studi Kasus Konsumen Produk Eiger Di Malang) - Hendra Irawan; Agus Widarko; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractAlong with the development of today's industry, the level of competition is getting tighter and tighter, where in Malang City there are many manufacturers who sell various kinds of brands both from within the country and abroad related to outdoor activities and now consumers are very concerned about product quality in making purchases. . This study aims to determine the effect of price, brand image, and product quality on buying interest. The case study in this research is consumers of Eiger products in Malang. The method used in this study is a quantitative method. The population in this study were all consumers of Eiger products in Malang and the sampling technique used in this study was using probability sampling technique using simple random sampling and obtained a sample of 100 respondents. The results of this study are price, brand image, and product quality simultaneously affect buying interest. Price has no effect on buying interest. Brand image has an effect on buying interest. and product quality affect buying interest. Keywords: Price, Brand Image, Product Quality, Purchase Interest.